Odpowiedzi

  • Użytkownik Zadane
2010-02-08T15:11:44+01:00
8x + (4x + 6y + 5) - (-5y + 8x -2) =20x+y-3
(2a + b) - (3a +6b -1) + a + 4b =11b-1
-3a -[ba - 4b - ( 5a - 5b)] =-2a+ba-11b
3 (a-3b) - 4 ( 2b - 4- x ) =3a-9b-8b+16+4x=3a-b+16+4x
-5 (4a - 3b) - 4 ( 5a - 5b ) =-20a+15b-20a+20b=-40a+35b
3 (2x - 3y) +2 (3x -5y - 1 =6x-9y+6x-10y-2=12x-y-2
Najlepsza Odpowiedź!
2010-02-08T15:26:07+01:00
8x + (4x + 6y + 5)-(-5y + 8x -2) = 8x + 4x + 6y + 5 +5y-8x+2=4x+11y+7

(2a + b) - (3a +6b -1) + a + 4b = 2a+b-3a-6b+1+a+4b=-b+1

-3a -[ba - 4b - ( 5a - 5b)] =-3a -ba +4b - 5a + 5b = -8a+9b-ba

3 (a-3b) - 4 ( 2b - 4- x ) = 3a+9b -8b+16 +4x= 3a-b+16+4x

-5 (4a - 3b) - 4 ( 5a - 5b ) =-20a - 15b -20a+20b= 5b

3 (2x - 3y) +2 (3x -5y - 1) = 6x-9y +6x -10y-2= -19y-2